At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To solve the given system of equations using the elimination method, follow these detailed steps:
The system of equations is:
1. [tex]\( 4x + 10y = -30 \)[/tex]
2. [tex]\( 5x + 11y = -27 \)[/tex]
### Step 1: Align the coefficients for one of the variables.
Let's eliminate [tex]\(x\)[/tex] by aligning the coefficients. We'll multiply the first equation by 5 and the second equation by 4, so that the coefficients of [tex]\(x\)[/tex] will be the same.
1. [tex]\( 4x + 10y = -30 \)[/tex] [tex]\( \times 5 \)[/tex] becomes [tex]\( 20x + 50y = -150 \)[/tex]
2. [tex]\( 5x + 11y = -27 \)[/tex] [tex]\( \times 4 \)[/tex] becomes [tex]\( 20x + 44y = -108 \)[/tex]
Now we have:
[tex]\[ 20x + 50y = -150 \][/tex]
[tex]\[ 20x + 44y = -108 \][/tex]
### Step 2: Subtract one equation from the other to eliminate [tex]\(x\)[/tex].
Subtract the second equation from the first:
[tex]\[ (20x + 50y) - (20x + 44y) = -150 - (-108) \][/tex]
[tex]\[ 20x + 50y - 20x - 44y = -150 + 108 \][/tex]
[tex]\[ 6y = -42 \][/tex]
### Step 3: Solve for [tex]\(y\)[/tex].
[tex]\[ 6y = -42 \][/tex]
[tex]\[ y = \frac{-42}{6} \][/tex]
[tex]\[ y = -7 \][/tex]
### Step 4: Substitute [tex]\(y\)[/tex] back into one of the original equations to solve for [tex]\(x\)[/tex].
Substitute [tex]\( y = -7 \)[/tex] into the first equation:
[tex]\[ 4x + 10(-7) = -30 \][/tex]
[tex]\[ 4x - 70 = -30 \][/tex]
[tex]\[ 4x = -30 + 70 \][/tex]
[tex]\[ 4x = 40 \][/tex]
[tex]\[ x = \frac{40}{4} \][/tex]
[tex]\[ x = 10 \][/tex]
### Conclusion
The solution to the system of equations is [tex]\( (x, y) = (10, -7) \)[/tex].
Thus, the correct answer is:
[tex]\[ (10, -7) \][/tex]
The system of equations is:
1. [tex]\( 4x + 10y = -30 \)[/tex]
2. [tex]\( 5x + 11y = -27 \)[/tex]
### Step 1: Align the coefficients for one of the variables.
Let's eliminate [tex]\(x\)[/tex] by aligning the coefficients. We'll multiply the first equation by 5 and the second equation by 4, so that the coefficients of [tex]\(x\)[/tex] will be the same.
1. [tex]\( 4x + 10y = -30 \)[/tex] [tex]\( \times 5 \)[/tex] becomes [tex]\( 20x + 50y = -150 \)[/tex]
2. [tex]\( 5x + 11y = -27 \)[/tex] [tex]\( \times 4 \)[/tex] becomes [tex]\( 20x + 44y = -108 \)[/tex]
Now we have:
[tex]\[ 20x + 50y = -150 \][/tex]
[tex]\[ 20x + 44y = -108 \][/tex]
### Step 2: Subtract one equation from the other to eliminate [tex]\(x\)[/tex].
Subtract the second equation from the first:
[tex]\[ (20x + 50y) - (20x + 44y) = -150 - (-108) \][/tex]
[tex]\[ 20x + 50y - 20x - 44y = -150 + 108 \][/tex]
[tex]\[ 6y = -42 \][/tex]
### Step 3: Solve for [tex]\(y\)[/tex].
[tex]\[ 6y = -42 \][/tex]
[tex]\[ y = \frac{-42}{6} \][/tex]
[tex]\[ y = -7 \][/tex]
### Step 4: Substitute [tex]\(y\)[/tex] back into one of the original equations to solve for [tex]\(x\)[/tex].
Substitute [tex]\( y = -7 \)[/tex] into the first equation:
[tex]\[ 4x + 10(-7) = -30 \][/tex]
[tex]\[ 4x - 70 = -30 \][/tex]
[tex]\[ 4x = -30 + 70 \][/tex]
[tex]\[ 4x = 40 \][/tex]
[tex]\[ x = \frac{40}{4} \][/tex]
[tex]\[ x = 10 \][/tex]
### Conclusion
The solution to the system of equations is [tex]\( (x, y) = (10, -7) \)[/tex].
Thus, the correct answer is:
[tex]\[ (10, -7) \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.